2022
DOI: 10.1093/milmed/usac183
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Controlled Trial of Ketamine and Moderate Sedation for Outpatient Endoscopy in Adults

Abstract: Introduction Ketamine is an effective sedative agent in a variety of settings due to its desirable properties including preservation of laryngeal reflexes and lack of cardiovascular depression. We hypothesized that ketamine is an effective alternative to standard moderate sedation (SMS) regimens for patients undergoing endoscopy. Materials and Methods We conducted a randomized controlled trial comparing ketamine to SMS for ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…For patients with non-catecholamine-dependent, severe congestive heart failure, analgosedation was performed with ketamine and midazolam [ 11 , 17 , 18 , 23 , 24 ] by a second experienced bronchologist.…”
Section: Methodsmentioning
confidence: 99%
“…For patients with non-catecholamine-dependent, severe congestive heart failure, analgosedation was performed with ketamine and midazolam [ 11 , 17 , 18 , 23 , 24 ] by a second experienced bronchologist.…”
Section: Methodsmentioning
confidence: 99%
“…7 In another randomized clinical trial, surgical patients undergoing a risk-based protocol for reduced intensity of overnight vital signs reported fewer vital sign-associated disruptions and a trend towards improved sleep. 17 Several retrospective studies in different medical contexts have suggested that routine overnight vital sign checks only rarely lead to the diagnosis of clinically significant events. 18–20 However, data concerning this important clinical issue remain limited, particularly with regard to postoperative surgical patients.…”
mentioning
confidence: 99%